Human/Elephant/Mobility and Nomadic Life in a Modern World - Chaiwan, Saowaree; Panyagaew, Wasan (Journal of Social Sciences, Chiang Mai University, 2019)
In Thai society human and elephant have long lived and interacted to each other for centuries. It is embedded in a social life of people, particularly in a mahout community. In some areas of northern and north eastern Thailand, a community raise and domesticate an elephant for its labor use. The mahouts who have knowledge and skills to capture this wild animal, domesticating and training these elephants for labor use. The intimated interactions between the mahouts and the elephants are reflected in their belief and ritual conducts. In this article we present a survey research finding, from the research project “Socio-economic profile of Thai mahouts in Thai tourism industry”, and additional ethnographic data from multi-sited fieldworks, conducted from August 2017 – April 2018, covering an elephant camp located in the 6 main tourism provinces of Chonburi, Phuket, Ayutthaya, Kanchanaburi, Surin and Chiang Mai. We will show that most of the mahouts who work in these elephant camps, although they are not owned the elephants, almost all of them have a cultural background from the mahout community, a traditional mahout. This group of Thai traditional mahout have engaged in elephant raising and training it for labor use. Whereas some other new groups, a mahout worker, who never involved with elephant raising before entering to the elephant camps, as a worker, particularly these mahout workers are a minority and cross border migrants. From the neighboring countries. Both groups of these mahouts, nevertheless, share together that they did not have a high modern education. Working as a mahout at the tourism elephant camps, however, requires a special skill, practical knowledge accumulated from experienced work and love and engagement with the elephants. The expansion of tourism based elephant camp business, in the famous tourist cities of Thailand, inevitably creates a new form of nomadic life among the mahouts in these modern days. These mahouts, the modern nomads we argue, must leave their home villages to work in the tourism based elephant camps, both in the main tourist cities of Thailand, such as Pattaya, Phuket, Chiang Mai, and in the foreign countries.